Acute general surgery in Canada: a survey of current handover practices - Johner, Amanda M. (Canadian Medical Association, 2013)
BACKGROUND: Today’s acute care surgery (ACS) service model requires multiple handovers to incoming attending surgeons and residents. Our objectives were to investigate current handover practices in Canadian hospitals that have an ACS service and assess the quality of handover practices in place. METHODS: We administered an electronic survey among ACS residents in 6 Canadian general surgery programs. RESULTS: Resident handover of patient care occurs frequently and often not under ideal circumstances. Most residents spend less than 5 minutes preparing handovers. Clinical uncertainty owing to inadequate handover is most likely to occur during overnight and weekend coverage. Almost one-third of surveyed residents rate the overall quality of the handovers they received as poor. CONCLUSION: Handover skills must be taught in a systematic fashion. Improved resident communication will likely decrease loss of patient information and therefore improve ACS patient safety.